2020
DOI: 10.3390/ijms22010195
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Steroidogenic Factor 1 (sf-1) and 17α-Hydroxylase/Lyase (cyp17α) Promoters in Yellow Catfish Pelteobagrus fulvidraco

Abstract: The present study was performed to clone and characterize the structures and functions of steroidogenic factor 1 (sf-1) and 17α-hydroxylase/lyase (cyp17α) promoters in yellow catfish Pelteobagrus fulvidraco, a widely distributed freshwater teleost. We successfully obtained 1981 and 2034 bp sequences of sf-1 and cyp17α promoters, and predicted the putative binding sites of several transcription factors, such as Peroxisome proliferator-activated receptor alpha (PPARα), Peroxisome proliferator-activated receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Thus, 100 nM T3 was adopted in the current study (Figure 6a). To study the responsiveness of the Mc4r promoter to thyroxine and leptin, HEK293T cells were incubated with 100 nM T3 or 200 ng/mL leptin (Lv et al, 2020) for 24 h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 100 nM T3 was adopted in the current study (Figure 6a). To study the responsiveness of the Mc4r promoter to thyroxine and leptin, HEK293T cells were incubated with 100 nM T3 or 200 ng/mL leptin (Lv et al, 2020) for 24 h.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal concentration of T3 was screened by the effect of T3 on the activity of the Mc4r promoter. After transfection of Mc4r promoter 5′‐deletion fragment plasmids (pGl3‐41/+321, pGl3‐282/+321, pGl3‐908/+321, and pGl3‐1708/+321), pcDNA3.1(+)‐NKX2.1, and Mut‐ Mc4r ‐NKX2.1, the transfected HEK293T cells were incubated using 0 and 200 ng/mL leptin (Lv et al, 2020), and optimal concentrations of T3, respectively. Collect cell samples after 24 h, the cells were lysed and harvested for the luciferase activities according to the procedure above.…”
Section: Methodsmentioning
confidence: 99%
“…PPARγ, STAT3 and FOXL2 regulate the transcription of key enzymes in steroidogenesis [ 13 , 38 ]. The present study found that PPARγ significantly increased the transcriptional activity of TSPO promoter, while STAT3 and FOXL2 decreased TSPO transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Yellow catfish Pelteobagrus fulvidraco , widely distributed freshwater fish, is an important economic fish in some Asian countries due to the high economic value and delicious meat quality. At present, studies were scarce on the regulation of steroidogenesis for the fish species [ 13 ]. To this end, we cloned and characterized the cDNA and promoter sequences of TSPO and SMAD4 genes, and determined their mRNA tissue expression and investigated their transcriptional regulation in yellow catfish.…”
Section: Introductionmentioning
confidence: 99%
“…The primers for the plasmids construction were presented in Table S2. In addition, The overexpression plasmids of PPARα, PPARγ and STAT3 were obtained from our previous studies (Lv et al 2021).…”
Section: Promoter Cloning and Plasmids Constructionmentioning
confidence: 99%